A Statistical Study to the Impact of Advertisement on the Youth of the Capital of Azad Kashmir - ANWAR, Syed Masroor; SALEEM, Azhar; KHAN, A Qadeer; NAQVI, Syed Kafait Hussain; BUKHARI, Syed Shujaht (Asian Journal of Empirical Research, 2013)
The present research is conducted to study the views of youngsters about the role of advertisement in district Muzaffarabad, Azad Kashmir. We took the sample of 200 by using stratified random sampling from total population consists of ten main colleges of District Muzaffarabad. For analysis, we have used the chi-square test of association, frequency distribution and graphical method. According to the survey, we came to know that females are attracted by the advertisements more as compared to the males. From the hypothesis testing we came to know that gender and female representation are associated. We intended to know while buying a product, which characteristic of a product is considered the most and we came out with the finding that most customers consider both the price and quality of a product while buying it from the market and mostly, television is used as mode of advertisement Azad Kashmir. The study reveals that if there is a representation of famous personality in ads, the people consider that product is reliable and expensive by using. A large number of people think that ads reflect our culture to some extent and common idea in a glamorous way and they consider ads an exaggeration.